استخدام الكتيب الجيبي لمادة اللغة العربية في تحسين مهارة القراءة لطلاب الصف السابع في مدرسة بستان العلوم الإعدادية الإسلامية - Sholahuddinh, Muhammad Syafii; Lubis, Zulfahmi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to examine the use of Arabic language pocket books in improving the qiro'ah (reading) skills of seventh grade students at MTs Swasta Bustanul Ulum. This research uses the Classroom Action Research (PTK) method. This Classroom Action Research (PTK) model was carried out with 2 cycles consisting of four stages of activity, namely the planning stage, the implementation stage, the observation/observation stage and the reflection stage. Data collection techniques in this study include tests and observations. While the instruments in this study were in the form of test question sheets and student learning observation sheets. The data analysis technique used quantitative data analysis techniques and qualitative data. The results showed that the average student activity and ability of qiro'ah learning outcomes of VII grade students of MTs Swasta Bustanul Ulum in learning Chapter 6 with the material من يوميات الأسرة, with the use of pocket books of Arabic language subjects in the first cycle observation obtained the average activity of qiro'ah ability based on student learning outcomes is 42% (less active) and has increased in Cycle II which is 76% (active). In this case it can be proven that there is an increase in percentage from cycle I and cycle II by 34% and from the previous results which were classified in the less active category in cycle I to the active category in cycle II. For learning outcomes in the post-test cycle I, the average completeness obtained was 60% as many as 12 students who exceeded the KKM, in cycle II the average post-test completeness was 80% as many as 16 students who exceeded the KKM. The average post-test completeness in cycle II has exceeded 5% of the 75% success indicator. In this case it can be proven that there is an increase in percentage from cycle I and cycle II which is 20%. So it can be concluded that the use of pocket book media in Arabic language subjects can increase the activity and ability of qiro'ah based on the learning outcomes of VII grade students of MTs Swasta Bustanul Ulum.